Bridging the Gap: A Dual-Perspective Analysis of Audio-Visual Material Integration in Indonesian EFL Speaking Classrooms - Fikra Afdhali; Utami Dewi; Farida Repelita Waty BR Kembaren (MASI Mandiri Edukasi, 2026)
The integration of English audio-visual (AV) materials has been widely promoted as an effective approach for enhancing speaking skills in English as a Foreign Language (EFL) contexts; however, a persistent gap remains between its theoretical potential and classroom implementation in Indonesia. This qualitative case study aims to investigate perceptions and challenges of using AV materials for speaking skill development, examining both student and teacher perspectives. The study employed an applied qualitative research design, collecting data through Google Forms, classroom observations, and document analysis, involving two English teachers and 13 students at a private language institute in Lhokseumawe, Indonesia. Thematic analysis revealed a systemic misalignment between stakeholders. Students perceived AV materials as engaging, anxiety-reducing, and essential for accessing authentic language input, and they expressed a strong preference for interactive and creative speaking activities. In contrast, teachers, despite recognizing the pedagogical value of AV materials, faced significant constraints, including limited preparation time, unstable technological infrastructure, exam-oriented curricular pressures, and insufficient Technological Pedagogical Content Knowledge (TPACK). This TPACK deficiency led to predominantly input-focused and pedagogically simplified use of AV materials, limiting opportunities for meaningful spoken output. The study concludes that the primary barrier to effective AV integration lies not in technological access but in interconnected institutional, professional, and curricular constraints. To address this gap, the study proposes a tripartite framework consisting of institutional support re-engineering, TPACK-oriented professional development, and curricular realignment to legitimize AV-mediated speaking practice. These findings provide context-sensitive recommendations for transforming AV use from passive consumption into active speaking production in Indonesian EFL classrooms.